Strategi Komunikasi Yayasan Sedekah Ngider Indonesia Pada Program Kampung Sedekah (Studi Kasus Pada Kelurahan Susukan Jakarta Timur) - Putri, Adinda Shelsabella; Susanti, Endang; Ekasari, Retno; Utama, Dedy Kusna (LUGAS Jurnal Komunikasi, 2024)
The ineffectiveness of the communication process has led to the public misconception that the Kampung Sedekah program is an initiative established by Susukan Village, in fact it is a program run by the Ngider Indonesia Charity Foundation. This study aims to identify and analyze the communication strategy used in the Kampung Sedekah program, employing the persuasive communication strategy theory proposed by Melvin L. DeFleur and Sandra J. Ball-Rokeach, which includes psychodynamic strategies, sociocultural persuasion, and meaning construction. This research uses a descriptive qualitative approach, utilizingin-depth interviews, observation, and document analysis for data collection. The findings show that the Ngider Indonesia Charity Foundation implements three communication strategies aligned with the persuasive communicationtheory. Challenges in the persuasive communication and socialization processes are primarily due to the lack of trust from local officials in the Kampung Sedekah program and the absence of direct community engagement by the foundation. To address these issues, the foundation should engage directly with the community, carefully considering the appropriate timing and venue for socialization efforts, and facilitate regular meetings between the foundation and the community to foster good relations and establish effective communication.